UDP-Glycosyltransferases and Albendazole Metabolism in the Juvenile Stages of Haemonchus contortus - Kellerová, Pavlína; Navrátilová, Martina; Nguyen, Linh Thuy; Dimunová, Diana; Raisová Stuchlíková, Lucie; Štěrbová, Karolína; Skálová, Lenka; Matoušková, Petra (Frontiers in Physiology, 2020)
The nematode Haemonchus contortus, a gastrointestinal parasite of ruminants, can severely burden livestock production. Although anthelmintics are the mainstay in the treatment of haemonchosis, their efficacy diminishes due to drug-resistance development in H. contortus. An increased anthelmintics inactivation via biotransformation belongs to a significant drug-resistance mechanism in H. contortus. UDP-glycosyltransferases (UGTs) participate in the metabolic inactivation of anthelmintics and other xenobiotic substrates through their conjugation with activated sugar, which drives the elimination of the xenobiotics due to enhanced solubility. The UGTs family, in terms of the biotransformation of commonly used anthelmintics, has been well described in adults as a target stage. In contrast, the free-living juvenile stages of H. contortus have attracted less attention. The expression of UGTs considerably varies throughout the life cycle of the juvenile nematodes, suggesting their different roles. Furthermore, the constitutive expression in a susceptible strain with two resistant strains shows several resistance-related changes in UGTs expression, and the exposure of juvenile stages of H. contortus to ABZ and ABZSO (in sublethal concentrations) leads to the increased expression of several UGTs. The anthelmintic drug albendazole (ABZ) and its primary metabolite ABZ-sulfoxide (ABZSO) biotransformation, tested in the juvenile stages, shows significant differences between susceptible and resistant strain. Moreover, higher amounts of glycosidated metabolites of ABZ are formed in the resistant strain. Our results show similarly, as in adults, the UGTs and glycosidations significant for resistance-related differences in ABZ biotransformation and warrant further investigation in their individual functions.